Utility of Air Bladder-Derived Nanostructured ECM for Tissue Regeneration - Wang, Jianwei; Chen, Jiayu; Ran, Yongfeng; He, Qianhong; Jiang, Tao; Li, Weixu; Yu, Xiaohua (Frontiers in Bioengineering and Biotechnology, 2020)
Exploration for idea bone regeneration materials still remains a hot research topic due to the unmet clinical challenge of large bone defect healing. Bone grafting materials have gradually evolved from single component to multiple-component composite, but its functions during bone healing still only regulate one or two biological process. Therefore, there is an additional need to develop novel materials with more complex composition, which convey multiple biological functions during bone regeneration. Here we report an naturally nanostructured ECM based composite scaffold derived from fish air bladder and combined with dicalcium phosphate (DCP) microparticles to form a new type of bone grafting material. The DCP/acellular tissue matrix (DCP/ATM) scaffold demonstrated porous structure with porosity over 70% and great capability of absorbing water and other biologics. In vitro cell culture study showed that DCP/ATM scaffold could better support osteoblast proliferation and differentiation in comparison with DCP/ADC, which is made from acid extracted fish collagen. Moreover, DCP/ATM also demonstrated more potent bone regenerative properties in a rat calvarial defect model, indicating incorporation of ECM based matrix in the scaffolds could better support bone formation. Taken together, this study demonstrates a new avenue towards the development of new type of bone regeneration biomaterial utilizing ECM as its key components.